2020
DOI: 10.1002/jcc.26400
|View full text |Cite
|
Sign up to set email alerts
|

Block deformation analysis: Density matrix blocks as intramolecular deformation density

Abstract: Block deformation analysis as deformation density of atomic orbitals is introduced to analyze intramolecular interactions. In this respect, density matrix blocks in terms of natural atomic orbitals are employed to find interacting and noninteracting multicenter subsystem and extract the corresponding deformation density. Eigenanalysis of this deformation density is performed to result eigenvalues and eigenorbitals as displaced charge due to the intramolecular interaction and orbital space responsible for charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The WBI is the addition of the square of an off-diagonal density matrix element between the atoms, and it is determined as follows WBI = prefix∑ K P jk 2 = 2 P jj P jk 2 where P jk represents the density matrix element and P jj the changing density in the atomic orbital. There is no significant difference between the net bonding or anti-bonding type of element of the density matrix in the WBI …”
Section: Computational Detailsmentioning
confidence: 97%
See 1 more Smart Citation
“…The WBI is the addition of the square of an off-diagonal density matrix element between the atoms, and it is determined as follows WBI = prefix∑ K P jk 2 = 2 P jj P jk 2 where P jk represents the density matrix element and P jj the changing density in the atomic orbital. There is no significant difference between the net bonding or anti-bonding type of element of the density matrix in the WBI …”
Section: Computational Detailsmentioning
confidence: 97%
“…There is no significant difference between the net bonding or anti-bonding type of element of the density matrix in the WBI. 60 …”
Section: Computational Detailsmentioning
confidence: 99%
“…For all types of deformation densities, spectral decomposition of normalΔρ$$ \Delta \rho $$ can be grouped into two components concerning the corresponding eigenvalues' signs [67–70]. When analyzing deformation density, the eigenvalues have a special characteristic that allows for assigning eigenorbitals to specific occurrences.…”
Section: Computational Detailsmentioning
confidence: 99%
“…One of the major topics in the field of computational molecular electronics is analyzing charge distribution and its response to external electric field and several techniques are developed to analyze how these two components react to the applied voltage [10,63,64]. Also, electronic deformation density analysis is conducted for many chemical systems by present author including intermolecular and steric interaction analysis [65,66], capacitance of bilayer graphene flakes [30,60], and interatomic interaction [67]. In this respect, it has been shown that electronic deformations density can be used to analyze response of charge density to applied voltage [10].…”
mentioning
confidence: 99%